Design of a Web-Based Village Population Data Processing Information System: A Case Study of Tanah Merah Village Office, Pasir Penyu District - Farida Gultom; Adi Kurniawan; Sastra Wandi Nduru (Institute Of Advanced Knowledge and Science, 2026)
Population administration at the Tanah Merah Village Office, Pasir Penyu District, previously relied on conventional records that created duplicate data, inconsistent information, slow retrieval, and delayed report preparation. This study designed and implemented a web-based population data processing information system using observation, interviews, literature review, and the waterfall development model. Requirements were translated into use-case, activity, and class diagrams and a MySQL database. The implemented PHP-based system provides administrator authentication, user management, population and destination records, move-out requests, online birth-certificate registration, death-certificate registration, monitoring, document-completeness checks, and service outputs. Black-box testing covered seven navigation and data-management scenarios. All seven scenarios produced the expected results, yielding a 100% pass rate within the documented test scope. The system centralizes village records, reduces dependence on physical archives, and supports faster retrieval and reporting. Further work should evaluate usability, security, data validation, interoperability with higher-level civil-registration services, and operational performance after deployment.